2017
DOI: 10.1162/jocn_a_01050
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Object Shape and Surface Properties to Object Ensemble Representation in Anterior-medial Ventral Visual Cortex

Abstract: Abstract■ Our visual system can extract summary statistics from large collections of objects without forming detailed representations of the individual objects in the ensemble. In a region in ventral visual cortex encompassing the collateral sulcus and the parahippocampal gyrus and overlapping extensively with the sceneselective parahippocampal place area (PPA), we have previously reported fMRI adaptation to object ensembles when ensemble statistics repeated, even when local image features differed across imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The neural correlates underlying these processes remain vague. Though the Para-hippocampal Place Area (PPA) was associated with such processes, as found by Cant and Xu (2012, 2017, there is no differentiation of low-and high-level ensemble processing. Moreover, the mechanism of this unique processing is yet to be well understood, and a main question to be investigated in future research ishow and where are different ensembles processed?…”
Section: Discussionmentioning
confidence: 98%
“…The neural correlates underlying these processes remain vague. Though the Para-hippocampal Place Area (PPA) was associated with such processes, as found by Cant and Xu (2012, 2017, there is no differentiation of low-and high-level ensemble processing. Moreover, the mechanism of this unique processing is yet to be well understood, and a main question to be investigated in future research ishow and where are different ensembles processed?…”
Section: Discussionmentioning
confidence: 98%
“…Much behavioral evidence has been accumulated supporting this notion 6,7,1115,21,99103, but see 104 , although only a few recent fMRI studies have compared the neural representations of ensemble coding and individual processing 105107 . Cant and Xu 105,106 showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in’t Veld and de Gelder 107 showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals. However, unlike prior work that used stimuli of simple texture patches and objects 105,106 or that removed the information about facial expression of people from their blurred video clips 107 , the current study examined the distinct neutral substrates underlying the processing of facial crowds with varying emotional expressions compared to the processing of individual emotion expressions, providing evidence for distinct mechanisms supporting them.…”
Section: Discussionmentioning
confidence: 99%
“…Different patterns of hemispheric lateralization for the crowd emotion vs. individual emotion processing suggest that they may rely on qualitatively distinct systems. Much behavioral evidence has been accumulated supporting this notion (e.g., Alvarez & Oliva, 2008;Ariely, 2001;Cant, Sun, & Xu, 2015;Chong et al, 2008;Chong & Evans, 2011;Chong & Treisman, 2005;Choo & Franconeri, 2010;Corbett & Oriet, 2011;Haberman, Brady, & Alvarez, 2015;Haberman & Whitney, 2010;Im & Halberda, 2013;Leib et al, 2012;Parkes et al, 2001, but see Myczek & Simons, 2008, although only a few recent fMRI studies have compared the neural representations of ensemble coding and individual processing (e.g., , 2017Huis in't Veld & de Gelder, 2015). Xu (2015, 2017) showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in't Veld and de Gelder (2015) showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Xu (2015, 2017) showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in't Veld and de Gelder (2015) showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals. Because Cant and Xu (2015;2017) used the stimuli of simple texture patches and objects and Huis in't Veld and de Gelder (2015) removed the information about facial expression of people from their blurred video clips, the current study is the first to examine the distinct neutral substrates underlying the processing of facial crowds with varying emotional expressions and the processing individual faces and to show the evidence for distinct mechanisms supporting them.…”
Section: Discussionmentioning
confidence: 99%